PRICE SETTING IN NON-COMPETITIVE MARKETS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Price setting in non-competitive markets, characterized by imperfect competition or monopolistic conditions, presents unique challenges and implications for economic policy. This article explores the fundamental principles, mechanisms, and consequences of price setting in non-competitive markets. It discusses the factors influencing pricing decisions, the role of market power, and the implications for consumer welfare. Furthermore, it delves into the policy options available to regulate non-competitive markets and mitigate potential adverse effects.